Does the proficiency of serve reception influence the result of attack in elite volleyball and to what extent? - Stamm, R.; Stamm, M.; Tigane, J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Introduction Researchers have found an essential correlation between attack and the final result of the game in elite volleyball. Although attack is performed individually, it is preceded by cooperation between the setter and the receiver of serve (Drikos, Vagenas, 2011). Hughes and Daniel (2003) have found that proficiency of reception differentiates elite teams from mediocre ones.